PROGNOSTICATION OF RESIDUAL LIFE OF COLLAPSIBLE PIPELINE COMPOUNDS - Yu. N. Ribakov; O. D. Harlamova; R. I. Kyunnap; S. I. Chirikov (Научный вестник МГТУ ГА, 2016)
Highly informative method for determining the residual life of the compounds of collapsible oil pipelines on the actual condition of rubber O-rings is developed. Ratios and proposed formula for calculating the residual resource of quick couplings depending on the climatic region of operation are experimentally established.